2021
DOI: 10.2147/mder.s347763
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaver-Based Biomechanical Evaluation of a Novel Posterior Approach to Sacroiliac Joint Fusion: Analysis of the Fixation and Center of the Instantaneous Axis of Rotation

Abstract: Purpose The purpose of this study was to assess the stabilizing effect of a posterior joint fixation technique using a novel cortical allograft implant in unilateral and bilateral fixation constructs. We hypothesize that fixation would reduce the joint’s range of motion during flexion-extension, axial rotation, and lateral bending loads. We also hypothesize that fixation would shift the center of the instantaneous axis of rotation during the predominant flexion-extension motions towards the implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Further distinguishing it is that the procedure is performed minimally invasively, which allows it to be performed on an outpatient basis and does not require weight-bearing restrictions. 215 …”
Section: Minimally Invasive Spine Proceduresmentioning
confidence: 99%
“…Further distinguishing it is that the procedure is performed minimally invasively, which allows it to be performed on an outpatient basis and does not require weight-bearing restrictions. 215 …”
Section: Minimally Invasive Spine Proceduresmentioning
confidence: 99%
“…The ROM of each lumbar segment and SIJ in this intact FE model was compared to the data in several in vitro studies under equivalent loading conditions ( Panjabi et al, 1994 ; Lindsey et al, 2014 ; Cook et al, 2015 ; Cross et al, 2018 ; Ntilikina et al, 2020 ; Sayed et al, 2021 ). For the validation of ROM of each lumbar segment, the S1 was constrained, and pure moments of 7.5 Nm in flexion (FL), extension (EX), lateral bending (LB), and axial rotation (AR) were applied to the superior endplate (SEP) of L1.…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, Sayed et al published data on the biomechanical effects of a novel posterior sacroiliac approach. 11 In a cadaveric study evaluating six SI joint specimens, the effects of a posterior SIJ fixation utilizing a novel cortical allograft were studied. They found that unilateral and bilateral fixations generated sacroiliac joint ROM reductions in flexion-extension, lateral bending, and axial rotation.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, the novel cortical allograft allows for minimal motion at the implantation site, which promotes fusion in the region. 11 …”
Section: Introductionmentioning
confidence: 99%